A nanostructural basis for gloss of avian eggshells - Igic, Branislav; Fecheyr-Lippens, Daphne; Xiao, Ming; Chan, Andrew; Hanley, Daniel; Brennan, Patricia R L; Grim, Tomas; Waterhouse, Geoffrey I N; Hauber, Mark E; Shawkey, Matthew D (Journal of the Royal Society, Interface, 2015)
The role of pigments in generating the colour and maculation of birds' eggs is well characterized, whereas the effects of the eggshell's nanostructure on the visual appearance of eggs are little studied. Here, we examined the nanostructural basis of glossiness of tinamou eggs. Tinamou eggs are well known for their glossy appearance, but the underlying mechanism responsible for this optical effect is unclear. Using experimental manipulations in conjunction with angle-resolved spectrophotometry, scanning electron microscopy, atomic force microscopy and chemical analyses, we show that the glossy appearance of tinamou eggshells is produced by an extremely smooth cuticle, composed of calcium carbonate, calcium phosphate and, potentially, organic compounds such as proteins and pigments. Optical calculations corroborate surface smoothness as the main factor producing gloss. Furthermore, we reveal the presence of weak iridescence on eggs of the great tinamou (Tinamus major), an optical effect never previously documented for bird eggs. These data highlight the need for further exploration into the nanostructural mechanisms for the production of colour and other optical effects of avian eggshells.
Keywords: nanostruktury; Animals; Birds; structural colour; fosforečnany vápenaté; eggshell; Calcium Phosphates; pigmentace; uhličitan vápenatý; ptáci; ovum; Pigmentation; iridescence; Egg Proteins; tinamou; vaječné proteiny; gloss; Ovum; Nanostructures; zvířata; nanostructure; Calcium Carbonate